2013
DOI: 10.1038/ejhg.2012.282
|View full text |Cite
|
Sign up to set email alerts
|

Broad consent versus dynamic consent in biobank research: Is passive participation an ethical problem?

Abstract: In the endeavour of biobank research there is dispute concerning what type of consent and which form of donor–biobank relationship meet high ethical standards. Up until now, a ‘broad consent' model has been used in many present-day biobank projects. However it has been, by some scholars, deemed as a pragmatic, and not an acceptable ethical solution. Calls for change have been made on the basis of avoidance of paternalism, intentions to fulfil the principle of autonomy, wish for increased user participation, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
209
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(235 citation statements)
references
References 39 publications
3
209
0
4
Order By: Relevance
“…9,34,35 On the other hand, it is suggested that obtaining specific consent for every linkage or re-use may be overly burdensome or impossible, because this could result in costly and time-consuming procedures, poor recruitment, consent bias, or unwarranted intrusion into the private lives of individuals. [36][37][38] As a response to the difficulties in obtaining specific consent, adapted models of consent have been put into practice and discussed in the literature. The most common adaptations of consent are models that shift away from specific consent, such as 'broad consent', covering a broad range of future data uses.…”
Section: Adapting Consentmentioning
confidence: 99%
See 2 more Smart Citations
“…9,34,35 On the other hand, it is suggested that obtaining specific consent for every linkage or re-use may be overly burdensome or impossible, because this could result in costly and time-consuming procedures, poor recruitment, consent bias, or unwarranted intrusion into the private lives of individuals. [36][37][38] As a response to the difficulties in obtaining specific consent, adapted models of consent have been put into practice and discussed in the literature. The most common adaptations of consent are models that shift away from specific consent, such as 'broad consent', covering a broad range of future data uses.…”
Section: Adapting Consentmentioning
confidence: 99%
“…41 Others argue that broad consent is an ethically sound alternative for specific consent, although individuals are not given specific information about future research projects. 36,44 In the draft GDPR texts, the current conflicting positions of the Parliament and Council on this topic appear to be reflected. Some indicate that broad consent may not meet the conditions on consent as defined in the Parliament's draft GDPR, regarding the information that must be given to the individual.…”
Section: Adapting Consentmentioning
confidence: 99%
See 1 more Smart Citation
“…Genel onam, açık ya da sınırsız bir onam (blanket consent (açık onam); herhangi bir kısıtlama söz konusu olmadan, örneklerin ve verilerin sınırsız bir biçimde her türlü araştırma için kullanılması) türü değil; katı-lımcılar tarafından, gelecekte yapılması muhtemel, farklı amaçlardaki tıbbi araştırmalar için belirli bir çerçevede örneklerin ve verilerin kullanımına izin verildiği bir onam türüdür. 11,22 Söz konusu çerçe-vede, herhangi bir değişim meydana geldiğinde, katılımcılardan yeniden onam alınmalıdır. 22 Genel onam, araştırmacıların biyolojik örnek-ler ile bunlarla ilişkili verileri geniş bir yelpazedeki araştırma faaliyetlerinde kullanmak amacıyla katı-lımcılardan izin alınması sürecini tanımlamakta-dır.…”
Section: Genel Onamunclassified
“…11,22 Söz konusu çerçe-vede, herhangi bir değişim meydana geldiğinde, katılımcılardan yeniden onam alınmalıdır. 22 Genel onam, araştırmacıların biyolojik örnek-ler ile bunlarla ilişkili verileri geniş bir yelpazedeki araştırma faaliyetlerinde kullanmak amacıyla katı-lımcılardan izin alınması sürecini tanımlamakta-dır. 23 Pek çok ülkenin kılavuz ilkesine göre, projenin etik kurul tarafından onaylanması ve verilen onamın araştırmanın herhangi bir zamanında katılımcı tarafından geri alınabilir olması koşulları-nın yerine getirildiği durumlarda, gelecekte yapılması muhtemel araştırmalar için, genel onam alınması kabul edilebilir bir görüştür.…”
Section: Genel Onamunclassified